International law and the occupation of Germany 1944-1950 - Simpson, J.L. (The University of Edinburgh, 1951)
This book deals with the six years from 18th September, 1944 when the initial occupation of German territory in the West took place, to 19th September, 1950, when in their "Communique on Germany" the Foreign Ministers of France, the United Kingdom and the United States announced the opening of e. new phase in their relations with Germany. These Sir, years fall into three distinct periods. The first, the period of conventional belligerent occupation, lasted until the unconditional surrender of Germany on 5th June, 1945. On t i)a t d e t e the four Po Fees - France, the United Kingdom, the United States, end the U.S.S.R. - assumed supreme authority in respect of Germany. As a result the occupation ceased to have a conventional character, and a new period opened in the occupation of Germany. This, the second period, continued until 21st September, 1949, when the Federal Republic of Germany was established and the 'Western Occupying Powers limited the exercise of their supreme authority to certain defined fields. The first year of existence of the Federal Republic constitutes the third period. The distinctions between the three periods are explained in greater detail in the three corresponding Parts of this book.

The purpose of this book is to examine such of the measures end actions of the Powers in occupation of Germany as may be said to have significance for the international lawyer. Action taken by the Occupying Powers, or some of them, may be of significance for the international lawyer in e variety of ways. For example, the Occupying Powers concluded treaties which had a ''law- making" character, and treaties, which, though they may not have made international law, contain special features reflecting the unprecedented situation arising from the unconditional surrender of Germany. Again the actions of the Occupying Powers on the international plane throw light on the status of Germany in international law, and the relationship between her and the Occupying or of the Occupying Powers inter se.

To reduce whet aright otherwise have been too large a task to manageable proportions, it has been necessary to impose certain limitations on this work. First no attempt has been made to write a chronicle of the events of the period. Events are described only in so far as they appear to be material to the legal. issues. The facts stated are, as it were, the facts-in-law only. Secondly, the work is written from a British point of view. The actions on the international plane described here are those to which the Government of the United Kingdom or its representative in Germany (the Military Governor and later the High Commissioner) were party. This rule in practice excludes little of the action taken by France or the United States (or their representatives in Germany), since in rnatters of international import these Powers acted for the most part jointly with the United Kingdom. How much the rule .excludes of action taken by the U.S.S.R. on the international plane is a question which could be fully answered only by someone with access to Russian sources not available in the United Kingdom.

In presenting the material in Part II the choice lay between describing the various measures of the Occupying Powers in strict chronological order, or grouping them under certain broad headings. The latter method was chosen as making for greater clarity, although it has the disadvantage that the chronological relationship of matters dealt with in different chapters is not immediately apparent. To minimise this disadvantage cross-references have been given wherever they appear likely to assist, and a chronological table of international agreements and principal events has been appended.

The facts stated in this book are without exception facts, which in one form or another have been made public, and I bear sole responsibility for the opinions expressed.